Dampak Konseling Kelompok terhadap Kesehatan Mental Siswa SMA di Era Digital - Ramadhani, Amalia Tri; Aroyan, Annisa Fitri; Asmara, Asanda Louditta; Sekararum, Atiyq (TSAQOFAH, 2024)
The development of digital technology today has an influence on the mental health of adolescents, especially high school students. Students often face various challenges that can affect mental health, such as cyberbullying, egocentricity, fomo, etc. This study aims to analyze the impact of group counseling as an intervention to improve students' mental health in the digital era. This research method uses the literature study method by collecting, reviewing, and analyzing research articles from various sources relevant to group counseling. The results of this study show that group counseling has a good impact on students' mental health. Group counseling is said to be effective in overcoming students' mental health problems in the digital era. Group counseling is proven to be a potential guidance and counseling service strategy in improving the mental health of high school students in the digital era. Group counseling not only brings a good impact on mental health but also social skills and achieving potential to the fullest. This study concludes that the group counseling service strategy as a forum for sharing experiences and coping strategies in dealing with problems faced in the digital world.